Suvorexant for insomnia in older adults: a perspective review - Rajesh R Tampi; Geetha Manikkara; Silpa Balachandran; Piyush Taparia; Stephanie Hrisko; Shilpa Srinivasan; Deena J Tampi (BioExcel Publishing Ltd, 2018)
The aim of this review was to identify published randomized control trials (RCTs) that evaluated the efficacy and tolerability of suvorexant for the treatment of insomnia among older adults (≥65 years). A literature search was conducted of PubMed, MEDLINE, EMBASE, PsycINFO and Cochrane collaboration databases for RCTs in any language evaluating suvorexant for the treatment of insomnia in older adults. Additionally, references of full-text articles that were included in this review were searched for further studies. Data from three RCTs of suvorexant were included in this review. All the three studies fulfilled the criteria for being of good quality based on the items listed by the Center for Evidence Based Medicine (CEBM) for the assessment of RCTs. None of the three studies were conducted exclusively among older adults. However, they also included older individuals diagnosed with primary insomnia. These studies included a total of 1298 participants aged ≥65 years in age. Trial durations ranged from 3 months to 1 year. Available data from these studies indicate that suvorexant improves multiple subjective and polysomnographic sleep parameters for sleep onset and maintenance among older individuals with a diagnosis of primary insomnia and is generally well tolerated. Current evidence, although limited, indicates that suvorexant benefits older adults with primary insomnia and is generally well tolerated.